Assessment of the effects of skin microneedling as adjuvant therapy for facial melasma: A pilot study - Lima, Emerson V.A.; Lima, Mariana Modesto D.A.; Paixão, Mauricio Pedreira; Miot, Hélio Amante [UNESP] (Springer Nature, 2017)
Background: Melasma is a common chronic and relapsing acquired dyschromia. Skin microneedling was reported resulting sustained long-term improvement of recalcitrant melasma, however, the exact mechanism that promotes this skin lightening is not known. This study aimed to investigate clinical and histologic alterations promoted by skin microneedling in facial melasma. Methods: Open pilot trial including six women with facial refractory melasma submitted to two sessions of microneedling (1.5 mm) each 30 days followed by daily triple combination and broad-spectrum sunscreen. Comparison of pretreatment (T0) and 15 days after last microneedling procedure (T45) was made by standardized pictures, skin colorimetry, MASI, MELASQoL and histological parameters (haematoxylin-eosin, picrosirius-red, periodic acid Schiff and Fontana-Masson staining). Results: The age of the subjects varied from 34 to 46 years-old, the phototypes were III and IV (Fitzpatrick), and age of melasma onset was 20 to 38 years. Improvement of melasma was perceived in all subjects. There was a significant reduction of MASI score (-70%), MELASQoL (-55%) and increase in L* (+13%) colorimetric value (p < 0.03). All cases evidenced epithelium thickening, decrease in melanin pigmentation and densification of upper dermis collagen (p = 0.03). Patients were followed by 6 months under broad-spectrum sunscreen and triple combination without relapse. Conclusion: In addition to classic treatment (broad-spectrum sunscreen and triple combination), skin microneedling promoted clinical and histological improvement of refractory facial melasma.
Keywords: Masi; Melasma; Microneedling; Quality of life; Treatment